A study on the Filipino beliefs related to homes - Luna, Mark Anthony N. (1996.)
There are various Filipino beliefs existing at present. There are beliefs pertaining to how one should conduct himself/herself given a certain situation and there are beliefs pertaining to houses. It is the objective of this paper to determine which Filipino beliefs pertain to homes and how the beliefs affect the residents of the home. As a result, the younger generation today is often criticized by their more senior generation due to the manner in which they structure their houses. There are situations wherein, the structure of the house goes against the said beliefs, the senior generation become anxious because of the bad luck which might be brought upon them. At present, there are not enough documentation as to what Filipino beliefs are and how they are practiced in relation to houses thereby, posing difficulties to the people in determining the said beliefs.
Thesis (BID)--University of the Philippines Diliman
Keywords: Dwellings--Philippines--Interior decoration